IFPRI Malawi Monthly Maize Market Report, July 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The Monthly Maize Market Report was developed by researchers at IFPRI Malawi to provide clear and accurate information on the variation of maize prices in selected markets throughout Malawi. All prices are reported in Malawi Kwacha (K).